Model Resolusi Konflik Pemekaran Nagari - Fadil Haikal (Jurnal Sosiologi Andalas, 2019)
DPMN is the third party that helps to resolve the conflict between KAN Nagari Limo Koto and the so call Nagari preparatory government of Padang Laweh Selatan. In resolving the conflict, as a third party DPMN is able to resolve the conflict between the two parties. The objectives of this research are to describe the resolution of the conflict by both parties and by local governments and to describe the factors that enable DPMN to successfully resolve the conflicts. To achieve the research objectives, this study uses the Structuration Theory proposed by Anthony Giddens and qualitative research method. It was found that the conflict started in 2014 when Nagari Preparation Padang Laweh Selatan was in the process of expansion. At first the conflict was resolved by both parties by way of deliberations twice at the Koto VII sub-district office, but this was unsucessful. Then, after KAN Nagari Limo Koto sent a letter rejecting the expansion of the Nagari Preparation Padang Laweh Selatan to the Regent of Sijunjung, DPMN became the third party in resolving the conflict through conciliation. The conciliation process is carried out by: 1) forming a division team to resolve the conflict; 2) bringing together the two parties to the conflict; 3) collect data related to disputed ulayat lands; 4) trace the history of ulayat lands; 5) make the elite from KAN Nagari Limo Koto as partners in resolving conflicts; 6) make an agreement between the two parties through the Regional Regulation Ranperda; 7) disseminate the draft regional regulation to both parties. The factors that made it easier for DPMN to resolve the Conflict, namely: 1) making the regulations used in the process of dividing the preparatory village of South Padang Laweh as a reference; 2) actors DPMN and Elit Nagari Limo Koto understand that expansion aims to improve community welfare; 3) the conflict is not complicated.